Outcome of health education on HIV/AIDS knowledge, attitude and risky sexual behavior among commercial motorcyclists in Osogbo, Nigeria - Olakunle, Olarewaju Sunday; James, Bamidele; Olusola, Odu; Oluwatoyin, Olarewaju (International Journal Of Community Medicine And Public Health, 2017)
Background: Commercial motorcyclists in Nigeria are usually males within the reproductive age group and at risk of HIV/AIDS due to sub-optimal information on the cause and prevention as well as defective perception on HIV/AIDs, hence the need for continuous health education among this occupational group. Objective: To determine the effect of health education on knowledge, perception and risky sexual practices on HIV/AIDS among commercial motorcyclist in Osogbo, Osun state. Methods:A cross sectional descriptive survey with an intervention component was conducted in three stages between November, 2007 and June, 2008. One hundred and fifty respondents from both study and control groups were selected using a multi-stage sampling technique and interviewed with a pre-tested semi-structured questionnaire. The post-intervention stage was done 6 months later. Results:At post-intervention, study group (i.e. intervention group) exhibited a greater knowledge on correct methods of prevention and transmission of HIV/AIDS (P<0.05). Similarly, there was significant improvement in their attitudes towards people living with HIV/AIDS among respondents in the study group (P<0.05). In addition, the number of respondents having multi-sexual partners decreased from 24.7% pre-intervention to 14.2% six months post intervention.(P=0.01). Conclusions: This study has shown that health education can be effective in bridging the knowledge gap of HIV/AIDS among commercial motorcyclists. It is therefore recommended that continuous health education programmes on HIV/AIDS by relevant stakeholders be established for this category of occupation.